Bacterial Protein Characterization of Streptococcus agalactiae by SDS-page Method for Subclinical Mastitis Irradiated Vaccine Materials in Dairy Cattle - B.J. Tuasikal; I.W.T. Wibawan; F.H. Pasaribu; S. Estuningsih (PPIKSN-BATAN, 2012)
A study have been conducted to isolate and characterize bacterial protein S. agalactiae, which is antigenic and can be used to test immunogenicity of vaccine in order to manufacture irradiated mastitis (inflammation of the udder) vaccine in ruminant. The study aims to determine the Molecular Weight (MW) bacterial protein S. agalactiae irradiation, which can be used to test the nature of its antigenic caharacteristic. The character of S. agalactiae antigenic stimulates antibody induction of the immune system, in which case is the body's defense system against mastitis disease in cattle. In this study, irradiation of gamma ray is used to attenuate the pathogenicity of bacteria by reducing S. agalactiae antigenic caharacteristic. Previous research, in irradiation dose orientation before antigenic protein isolation of S. agalactiae, indicated that irradiation lethal dose to 50% (LD50) is 17 Gy. The characterization of S. agalactiae bacteria isolate using SDS-page method results in no significance different between irradiated and non-irradiated group, which indicated by MW range 75 – 100 kDa base on marker standard which used, or 99 kDa by the linier equation of Y = 11,60 – 0.05X (where Y = bands distance; X = MW standard protein); r2 = 0.99. In conclusion, 17 Gy irradiation dose does not impair antigenic property of S. agalactiae and therefore, can be applied to produce base material of irradiated vaccine for mastitis. Received: 04 May 2012; Revised: 27 November 2012; Accepted: 27 August 2012